Public policies against global warming - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2007)
Judged by the principle of intertemporal Pareto optimality, insecure property rights and the greenhouse effect both imply overly rapid extraction of fossil carbon resources. A gradual expansion of demand-reducing public policies - such as increasing ad-valorem taxes on carbon consumption or increasing subsidies for replacement technologies - may exacerbate the problem as it gives resource owners the incentive to avoid future price reductions by anticipating their sales. Useful policies instead involve sequestration, afforestation, stabilization of property rights and emissions trading. Among the public finance measures, constant unit carbon taxes and source taxes on capital income for resource owners stand out.
Keywords: O13; Q32; Q54; H23; 330; Klimaveränderung; Treibhausgas; Umweltpolitik; Aufforstung; Emissionshandel; Eigentumsrecht; Theorie